2015
DOI: 10.1016/j.rser.2014.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy gathers steam in South Africa

Abstract: South Africa's Renewable Energy Independent Power Producers Procurement Programme (the REI4P) is an extensive initiative to install 17.8 GW of electricity generation capacity from renewables-wind, solar, biomass, biogas and hydropower-over the period 2012 to 2030. Although at the outset the REI4P seemed an expensive option, designed only to deflect criticism of South Africa's high carbon footprint and excessive dependence on coal-based electricity generation, the escalating costs of the latter, the rapidly fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 26 publications
0
76
0
Order By: Relevance
“…The power generated by the independent power producers is fed to the national grid through a power purchase agreement. So far, this programme has proved to be successful in many respects including the diversification of power producers from a single to 64 power producers in the first three rounds of bidding, and reduction in the price of electricity [52]. There is an opportunity to replicate some of the successful factors in other developing countries, including those in the SADC region.…”
mentioning
confidence: 99%
“…The power generated by the independent power producers is fed to the national grid through a power purchase agreement. So far, this programme has proved to be successful in many respects including the diversification of power producers from a single to 64 power producers in the first three rounds of bidding, and reduction in the price of electricity [52]. There is an opportunity to replicate some of the successful factors in other developing countries, including those in the SADC region.…”
mentioning
confidence: 99%
“…The Renewable Energy Independent Power Producer Procurement Programme (REIPPPP), with the objective of increasing electricity supply while reducing dependency on fossil fuels [94], has led to a decrease in average solar PV prices from 2.76 R/kWh in 2011 to 0.79 R/kWh in 2015 [95] and the tariffs projected for 2030 had already been reached by 2014 [96]. The programme was initially criticised due to the competitive advantage of coal-generated electricity at the time and in the first round of bids, the average price of electricity from renewables was around 3.5 times higher than that of coal-based power generation [97]. However, increasing costs of coal-based electricity generation, rapidly decreasing costs of solar PV energy generation, along with an increasingly competitive bidding process of the programme have changed this [96,97].…”
Section: Potential Barriers To Implementationmentioning
confidence: 99%
“…The programme was initially criticised due to the competitive advantage of coal-generated electricity at the time and in the first round of bids, the average price of electricity from renewables was around 3.5 times higher than that of coal-based power generation [97]. However, increasing costs of coal-based electricity generation, rapidly decreasing costs of solar PV energy generation, along with an increasingly competitive bidding process of the programme have changed this [96,97].…”
Section: Potential Barriers To Implementationmentioning
confidence: 99%
“…Both of the above qualities are necessary for renewable energy related project planning and management and to ensure appropriate application and utilization of renewable energy technologies for local conditions. In the light of the above, the establishment of renewable energy programs such as South Africa's Renewable Energy Independent Power Producers Procurement Programme designed to reduce South Africa's carbon emissions depends on the availability of qualified human resource (Msimanga and Sebitosi, 2014;Baker, 2015;Walwyn and Brent, 2015). Jain et al (2002) reported that the government of Botswana through the ministry of minerals, energy and water affairs commissioned studies to assess the training in renewable energy in technical schools of Botswana to make recommendations toward the desired training programs and create facilities to meet the training needs.…”
Section: Review Of Advanced Education and Training In Renewable Energmentioning
confidence: 99%